2019
DOI: 10.1177/0892705719845712
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network modeling for prediction of cutting forces in turning unreinforced and reinforced polyamide

Abstract: Cutting force measurement in manufacturing is very important to optimize the machining process. The parameters, such as the type of material, feed rate, cutting speed, and cutting tool, affect the cutting forces in the turning operation. In this study, an artificial neural network (ANN) model is used to predict the cutting forces during the turning operation of unreinforced and reinforced polyamide (PA) with 30 v/v% carbon fibers using the cutting tools K15 and polycrystalline diamond (PCD). The cutting speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The effects of process parameters (Vc and f) on machinability characteristics, namely (Ra, Fz and Ks) have been studied. G. Özden et al [13] proposed an approach using (ANN) to predict the cutting force components when turning polyamides with and without reinforcement using two cutting tools (K15 and PCD). Based on the deviation indicators (R 2 and MAPE), they concluded that the predicted results are very close to experimental results.…”
Section: Silva Et Almentioning
confidence: 99%
“…The effects of process parameters (Vc and f) on machinability characteristics, namely (Ra, Fz and Ks) have been studied. G. Özden et al [13] proposed an approach using (ANN) to predict the cutting force components when turning polyamides with and without reinforcement using two cutting tools (K15 and PCD). Based on the deviation indicators (R 2 and MAPE), they concluded that the predicted results are very close to experimental results.…”
Section: Silva Et Almentioning
confidence: 99%
“…At this point, precision machining methods such as turning and milling play an important role for improving different forms of polymeric parts. 2124 Also, many parts and components are combined with riveting and bolting techniques for a composite-based complex manufacturing. These techniques are one of the main joining methods, and therefore drilling holes becomes mandatory to facilitate assembly in polymer or polymer-based composite parts.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial neural network (ANN) is observed as a useful modeling tool for varying parameters of the machining process. 3032 It is a statistical pattern that imitates the natural behavior of neurons. Gaitonde et al 33 discussed an ANN-based multilayer model of feedforward to investigate the cutting parameters of polyamide reinforced by glass fibers (PA66 GF30).…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes of this model reduced the cutting force by controlling speed and feed rate during machining. 31 It can provide several process properties with the most complicated analytical relationship about process parameters at the same time. Jenarthanan et al 34 established the ANN model by considering the varying parameters such as feed rate, the orientation of fiber, speed, and helix angle for prediction of engendered cutting force in milling of glass fiber reinforced polymer(GFRP).…”
Section: Introductionmentioning
confidence: 99%